Serum procalcitonin predicts mortality independently of the presence of ACLF in patients with cirrhosis and ascites hospitalized for suspicious infection and treated with empiric antibiotic therapy. (March 2023) - Bianchini, M.; Celsa, C.; Magro, B.; Cavani, G.; Giuffrida, P.; Battaglia, S.; Saltini, D.; Zanetto, A.; Indulti, F.; Guasconi, T.; Girardis, M.; Calvaruso, V.; et al.
Abstract : Introduction: Patients with cirrhosis and ascites are at high risk of infections, which increase mortality and trigger acute-on-chronic liver failure (ACLF). Aim: To evaluate procalcitonin (PCT) as risk factor for 28- and 90-day mortality in patients with decompensated cirrhosis with or without ACLF hospitalized for suspected infection and treated with empiric antibiotic therapy. Materials and Methods: Two-hundred thirty-seven patients with ascites admitted at two Italian referral centers were prospectively evaluated. Risk factors for 28- and 90-day mortality were assessed by multivariate competing risks analysis, with liver transplant (LT) as competing event. Results: Infection was confirmed in 83% of patients; 53% had ACLF; 88 (37%) died and 52 (22%) underwent LT within 90 days from admission. Creatinine [Hazard Ratio (HR)] 1.18, 95% Confidence Interval [95%CI] 1.01-1.38, p=0.039), grade III-IV hepatic encephalopathy (HR 2.32, 95%CI 1.15-4.65, p<0.018), septic shock (HR 2.77, 95%CI 1.39-5.53, p=0.004), baseline PCT>0.5 ng/mL (HR 4.10, 95%CI 1.24-13.38, p=0.021) or 48-hour PCT unfavorable course (HR 3.08, 95%CI 1.49-6.42, p=0.003) were risk factors for 28-day mortality by multivariate analysis (AUC 0.84). The same risk factors plus age (HR 1.03, 95%CI 1.01-1.05, p=0.001) were predictive for 90-day mortality (AUC 0.78). When ACLF was included in the multivariate model, instead of the single covariates, both ACLF and PCT (baseline levels and 48-hour course) were independently associated with 28- and 90-day mortality (AUC 0.83 and 0.72 respectively). When either baseline or 48-hour course PCT were combined with ACLF grade the prediction of 28- and 90- day mortality significantly increased. Conclusions: PCT both at baseline and 48-hour after starting empiric antibiotic treatment significantly predicts 28- and 90-day mortality in patients with decompensated cirrhosis presenting with or without ACLF at admission. Keywords : Decompensated cirrhosis, infections, empiric antibiotic treatment, ACLF, procalcitonin